Hubungan Faktor Fisika-Kimia Perairan Terhadap Kelimpahan Moluska di Area Keramba Jaring Apung Sistem Polikultur Teluk Awerange, Sulawesi Selatan - Amalia Aininnur; Sapto Purnomo Putro; Fuad Muhammad (Jurnal Akademika Biologi, 2015)
Fish farming using floating cage has been conducted for a long time in Indonesia. Despite the benefits of aquaculture to meet the needs of the human protein, aquaculture has potential impact on the aquatic environment, especially due to the impact  of  organic  enrichment.  This  study aims  to  determine  the  relationship  of  water  physical-chemical  on  the abundance of mollusks as a biological agent to determine the level of environmental disturbance. This research was conducted in the waters of the Awerange Gulf, South Sulawesi. Mollusks samples were taken from two stations, namely the reference area and polyculture cage area with twice the sampling time and three   replicates. Abiotic and biotic relationships conducted using multivariate approach (Principal Component Analysis / PCA, BIO-ENV) using Eucladian Distance matrix. Based on the results, there were 15 species consisting of 14 families and 2 classes (gastropods and bivalves). Families were most prevalent in both sites was Turritellidae. In general, water quality in the Awerange Gulf is considered normal at both locations. Results of ordination using PCA on abiotic factors indicated that the stations between reference area and polyculture cage area are clustered, implying the difference of both sites. BIO-ENV analysis results indicates that the abiotic factors that most influence the distribution and abundance of molluscs in the Awerange Gulf were DO, Carbon and Nitrogen contain (r = 0.457; BIO-ENV). Keywords : Mollusk, Polyculture Cage, Awerange Gulf, Abiotic Component